Functional Analysis of the Phosphate Transporter Gene MtPT6 From Medicago truncatula - Cao, Yuman; Liu, Jinlong; Li, Yuanying; Zhang, Jing; Li, Shuxia; An, Yunru; Hu, Tianming; Yang, Peizhi (Frontiers in Plant Science, 2021)
Phosphorus is one of the essential macronutrients required by plant growth and development, but phosphate resources are finite and diminishing rapidly because of the huge need in global agriculture. In this study, 11 genes were found in Phosphate Transporter 1 (PHT1) family of Medicago truncatula. Seven genes of PHT1 family were available by qRT-PCR. Most of them were expressed in roots, and almost all genes were induced by low phosphate stress in nodule. The expression of MtPT6 was relatively high in nodules and induced by low phosphate stress. The fusion expression of MtPT6 promoter-GUS gene in M. truncatula suggested that the expression of MtPT6 was induced in roots and nodules by phosphate starvation. In roots, MtPT6 was mainly expressed in vascular tissue and tips, and it was also expressed in cortex under low phosphate stress; in nodules, it was mainly expressed in vascular bundles, cortical cells and fixation zone cells. MtPT6 had a close relationship with other PHT1 family members according to amino acid alignment and phylogenetic analysis. Subcellular localization analysis in tobacco revealed that MtPT6 was localized to the plasma membrane. The heterologous expression of MtPT6 in Arabidopsis knockout mutants of pht1.1 and pht1.4 made seedlings more susceptible to arsenate treatment, and the phosphate concentrations in pht1.1 were higher in high phosphate condition by expressing MtPT6. We conclude that MtPT6 is a typical phosphate transporter gene and can promote phosphate acquisition efficiency of plants.